Patterns and Outcomes of Cutaneous Adverse Drug Reactions in a Hospital Based Study - Paudel, Upama; Parajuli, S; Pokhrel, DB (Nepal Journal of Dermatology, Venereology & Leprology, 2017)
Introduction : Drug reactions are one of the common reasons for admission in the Dermatological beds. Data on the culprit drugs and patterns of reaction are very scarce in Nepal. Objective:To determine the patterns of drug reactions admitted in Tribhuwan University (TU) Teaching hospital, the causes of drug reactions, duration of hospital stay, duration of steroid use and the outcome of the treatment. Material and Methods: This was a retrospective study done in TU Teaching Hospital. The admissions and discharge record of admitted patients from 15th April 2008 to 14th April 2012 were analyzed for the variables mentioned above. Results: There were 61 new patients of drug reactions; however only files of 42 patients could be studied.The mean age of the patients was 32.26 ± 15.26 with male to female ratio of 1.8:1. Stevens Johnson’s syndrome (35.7%) was the commonest cause of admission followed by drug induced erythroderma (16.7%) and toxic epidermal necrolysis (11.9%). Carbamazepine, Phenytoin and allopurinol were the most common drugs for the reactions. The median time for the appearance of the lesions was 20.07 days. The median duration of hospital stay was 7 days. Steroids were used for initial treatment for around 4.9 ± 1.7 days. 83.3% of the patients improved while 11.9% succumbed despite optimal management. Conclusion: Severe drug reactions were the common reasons for admissions in our hospital. Anti-epileptics were the leading cause for the reactions. Steroids were used for initial period and rapidly tapered off in short duration. Overall, the outcomes of the treatment were good.